Experimental and analytical evaluation of bending for mild steel - Azrulhafiq, Mohd Azizi (2012)
This report deals with analytical experimental and analytical evaluation of bending for Mild steel. Analytical method has been used in sheet metal bending analysis due to its simplistic method as compared simulation. However, the reliability of the method needs to be evaluated against experimental in term of measurement result. Nowdays, many analytical analyses is used to investigate the springback in sheet metal. In manufacturing industries especially, analytical analysis is used in making and determine the accurate dimension of die and punch of a machine. The analytical analysis is the most economical method in determine the springback compared by using real test and any software such as Finite element analysis. This report is done by using analytical analysis of springback using a material of mild steel AISI 1010 on V-bending process and also an experiment of V-bending. The experiment is conducted using 2 mm and 3mm thickness. The springback of mild steel AISI 1010 sheet was investigated using previous study of analytical analysis by Daw Kwei Leu. The effects of the normal anisotropy value R and the strain hardening exponent n on V bending of mild steel AISI 1010 have been studied. Eighteen specimens have been used in tensile test in determine the mechanical properties to be used in analytical analysis. An experiment of eighteen specimens of mild steel sheet were conducted in this experiment and the result were taken. The results of the experiment were compared with analytical analysis to validate the analytical method used. The result of the report show that the analytical method used is applicable but still need improvement and the normal anisotropy R and strain hardening exponent have affected the springback deformation.